DOWN TURN IN WOMEN’S SPORTS PARTICIPATION IN INTER-COLLEGE COMPETITION AT CH. DEVI LAL UNIVERISTY, SIRSA - Kumar, Ravinder (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2023)
Abstract The position of women in society has been at the center of discussions for decades. The concepts of gender mainstreaming to empower women, gender equality and gender equity were identified as key factors in promoting women’s quality of life. In the ancient Olympic Games, women were not allowed to participate, they were not even allowed to see the games. The overall concept has now changed days. The sports and sports program is a part of the entire educational system. The program of physical education and sports activities should be based on the interests and needs of the students, institutions and also the structure of the organization. University-level physical education classes should be sufficient for modern youth to acquire fine motor skills for the future development of women’s sports. The young women of the universities and colleges are the best prospects for the future to achieve top performance in the field of sports. It is acceptable that India’s achievements in physical education and sport are negligible. It is also accepted that the performance of Indian University. The youth are not even close to their counterparts in Europe and other nations. Ch.Devi Lal University, Sirsa has not yet achieved a prominent place in the inter-university competitions. The reason could be multiple and hence researchers say this is necessary in the present hour to find out the causes behind the lower participation of various college women teams in the inter-college competition of Ch.Devi Lal University, Sirsa. The purpose of the study is therefore an examination of the factors contributing to college women’s participation in the Intercollege Competition at Ch.Devi Lal University, Sirsa.